2022
DOI: 10.1161/circulationaha.121.058133
|View full text |Cite
|
Sign up to set email alerts
|

Taming Hypertension to Prevent Aortic Dissection: Universal Recognition of a “New Normal” Blood Pressure?

Abstract: cal community not only to understand the exponential relationship between intravascular tension and the risk of dissection but also to adjust blood pressure probably to the lowest tolerated level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[23] Poor blood pressure control is clearly associated with the occurrence of aortic dissection. [24,25] Studies have revealed that miR-202-3p targets ST2 to reduce the occurrence of essential hypertension. [26,27] Therefore, miRNA has potential significance as a diagnostic biomarker for AAD.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Poor blood pressure control is clearly associated with the occurrence of aortic dissection. [24,25] Studies have revealed that miR-202-3p targets ST2 to reduce the occurrence of essential hypertension. [26,27] Therefore, miRNA has potential significance as a diagnostic biomarker for AAD.…”
Section: Discussionmentioning
confidence: 99%